Pandangan Hak Asasi Manusia Terhadap Anak Sebagai Pelaku Tindak Pidana: Tinjauan Viktimologi - Teresa Amelya Putri; Adita Rizki Kurniawati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Children as perpetrators of criminal acts are often the subject of debate and special attention in the criminal justice system, in victimology studying the causes of victims and the consequences caused, victimology also helps us better understand the experiences and needs of crime victims, which in turn can help in improving the criminal justice system and providing better support to those who have become victims of crime. This type of research is socioyuridical with a non-doctrinal approach, which views law as a socio-empirical symptom. not only examines the normative aspects, but also the law as it is in reality. The approach method used is a normative juridical approach. analytical juridical descriptive research, with data sources of primary, secondary and tertiary legal materials, as well as those supported by primary data, and analyzed qualitatively juridical social environment greatly affects the development and growth of children. mass media can also have a bad impact on children if not given supervision. Another factor that needs special attention in the problem of criminal acts committed by child offenders is family factors. The role of the family as a factor in the causation of children's criminal acts is undeniable. Children involved in criminal offenses experience psychological and social impacts depending on various factors, namely the type of crime, the social environment and the criminal justice system.